2019
DOI: 10.1111/ijcp.13360
|View full text |Cite
|
Sign up to set email alerts
|

Patient expectation trends on receiving antibiotic prescriptions for respiratory tract infections: A systematic review and meta‐regression analysis

Abstract: Background Despite a variety of programs developed to control inappropriate antibiotic prescribing for viral infections, antibiotics are still prescribed excessively for Respiratory Tract Infections (RTI). The patient’s expectation to receive an antibiotic often influences the clinician’s decision and can lead to inappropriate antibiotic prescriptions. Our objective was to investigate the changes in patient expectations over time when presenting with symptoms of a respiratory infection. Methods We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
(140 reference statements)
6
25
0
Order By: Relevance
“…In addition, these three studies are older compared to other studies and this may in part explain the difference in results. This is consistent with the results of a recent systematic review that showed that the trend of patient expectation for receiving antibiotics for respiratory tract infections is declining over time on a global level [45]. Public knowledge and beliefs may have changed in recent years because of easy access to different sources of information through internet or media.…”
Section: Main Findings Of Study and Comparison With Previous Literaturesupporting
confidence: 90%
“…In addition, these three studies are older compared to other studies and this may in part explain the difference in results. This is consistent with the results of a recent systematic review that showed that the trend of patient expectation for receiving antibiotics for respiratory tract infections is declining over time on a global level [45]. Public knowledge and beliefs may have changed in recent years because of easy access to different sources of information through internet or media.…”
Section: Main Findings Of Study and Comparison With Previous Literaturesupporting
confidence: 90%
“…The model explains how patient expectation and provider's PPE during outpatient office visits has changed during the past 23 years. The simulation results for patient expectation to receive antibiotics for ARTI conditions in most age groups and regions, depicted a declining trend during the last two decades, which is confirmed in two other studies …”
Section: Discussionsupporting
confidence: 78%
“…13 There is consistent evidence that GPs are more likely to prescribe antibiotics when their patients are perceived to be expecting them. 8,[14][15][16] A systematic review found a generally positive association between physician perceptions of patient expectation and antibiotic prescription, 17 but some studies find evidence of a negative association between expectation and prescription 4 with evidence of inconsistency between physicians' perceptions and patients' desire for antibiotics. It is also well established that prescribing antibiotics increases the likelihood that patients will consult in future illness episodes, 18 raising the possibility that expectations are a consequence not a cause of antibiotic prescribing.…”
Section: Backg Rou N Dmentioning
confidence: 99%